Adaptive control law nonlinear synthesis for hydroturbine rotation frequency: principle of integral adaptation - A. A. Kuz’Menko (Известия высших учебных заведений: Проблемы энергетики)
Hydroturbine, like any complex system, operates under conditions of various parametrical perturbations as well as perturbations acted from the external environment. In case of worst perturbations, we need to build such laws to control the turbine, which would ensure the stabilization of the turbine rotor speed in the presence of such perturbations with minimum information about the structure of the external factors and the turbine stability. The obtained law of hydroturbine adaptive control provides the control target implementation, i.e. stabilization of the turbine rotor speed and suppression of piecewise constant perturbations due uncertainty of electrical power (the load). The novelty of the work is to construct a turbine rotor speed control law for its non-linear model, based on the principle of integrated adaptation of synergetic control theory, which provides adaptability to worst perturbation without constructing observers.